Alignments between e‐waste legislation and the Sustainable Development Goals: the United Kingdom, Brazil, and Ghana case studies. Issue 1 (3rd March 2022) - Lopes dos Santos, Kauê; Jacobi, Pedro Roberto
Abstract: The first two decades of the 21st century had a significant increase in e‐waste generation. While improper recycling technologies applied to this type of waste pose severe risks to the environment and human health, several e‐waste management legislation has been recently enforced worldwide, reaching 78 countries and covering 71% of the global population. In common, most of them aim to recycle minerals and plastic from the disposed waste of electric and electronic equipment (WEEE) to reinsert them in the industry, promoting the so‐called circular economy. From the comparative case study of countries that integrate the world‐system in different social and economic conditions – the United Kingdom (as core or developed country), Brazil (as semi‐periphery or emergent country), and Ghana (as periphery or developing country) –, this article aims to understand to what extent the national legislation on e‐waste management in these territories align with the Sustainable Development Goals 3, 6, 8, 11, 12, 14, and 15. This research has an exploratory approach and is methodologically structured as a controlled comparison of most different cases. Results reveal that selected legislation has different levels of alignment with SDG, ranging from generic mentions of social‐environmental topics to description of legal instruments to be enforced regarding environmental preservation, improvement of population's life quality, and changes in the unsustainable production, consumption, and disposal patterns. The article also seeks to contribute to the geographical debate by establishing the relation between e‐waste legislation and SDG, considering the territorial particularities of the case studies. Abstract : The article establishes dialogues between e‐waste regulation from three countries and the Sustainable Development Goals. The regulation models are distinct and promote, in each spatial context, different levels of dialogue with the SDGs.